Evidence of polygenic regulation of the physiological presence of neurofilament light chain in human serum - Herrera-Rivero, Marisol; Hofer, Edith; Maceski, Aleksandra; Leppert, David; Benkert, Pascal; Kuhle, Jens; Schmidt, Reinhold; Khalil, Michael; Wiendl, Heinz; Stoll, Monika; Berger, Klaus (Frontiers in Neurology, 2023)
Introduction The measurement of neurofilament light chain (NfL) in blood is a promising biomarker of neurological injury and disease. We investigated the genetic factors that underlie serum NfL levels (sNfL) of individuals without neurological conditions. Methods We performed a discovery genome-wide association study (GWAS) of sNfL in participants of the German BiDirect Study (N = 1,899). A secondary GWAS for meta-analysis was performed in a small Austrian cohort (N = 287). Results from the meta-analysis were investigated in relation with several clinical variables in BiDirect. Results Our discovery GWAS identified 12 genomic loci at the suggestive threshold ((p < 1 × 10−5). After meta-analysis, 7 loci were suggestive of an association with sNfL. Genotype-specific differences in sNfL were observed for the lead variants of meta-analysis loci (rs34523114, rs114956339, rs529938, rs73198093, rs34372929, rs10982883, and rs1842909) in BiDirect participants. We identified potential associations in meta-analysis loci with markers of inflammation and renal function. At least 6 protein-coding genes (ACTG2, TPRKB, DMXL1, COL23A1, NAT1, and RIMS2) were suggested as genetic factors contributing to baseline sNfL levels. Discussion Our findings suggest that polygenic regulation of neuronal processes, inflammation, metabolism and clearance modulate the variability of NfL in the circulation. These could aid in the interpretation of sNfL measurements in a personalized manner.